Posterolaterally displaced and flexion-type supracondylar fractures are associated with a higher risk of open reduction. Issue 5 (September 2016) - Novais, Eduardo N.; Carry, Patrick M.; Mark, Bryan J.; De, Sayan; Miller, Nancy H.
Abstract : To identify factors predictive of the risk of conversion from closed to open reduction. International Classification of Disease-9 codes were used to identify completely displaced pediatric supracondylar humerus fractures that were subjected to planned closed reduction and percutaneous pinning. Clinical and radiographic variables were retrospectively collected. Compared with posterior extension fractures, flexion (risk ratio: 34.1, 95% confidence interval: 8.1–143.6, P <0.0001) and posterolateral extension (risk ratio: 6.0, 95% confidence interval: 1.3–27.5, P =0.0221) fractures were significantly more likely to undergo conversion from closed to open reduction. The direction of displacement should be considered during the preoperative evaluation of supracondylar fractures.